2023
DOI: 10.3390/ijms24021631
|View full text |Cite
|
Sign up to set email alerts
|

The Old and the New: Cardiovascular and Respiratory Alterations Induced by Acute JWH-018 Administration Compared to Δ9-THC—A Preclinical Study in Mice

Abstract: Several new psychoactive substances (NPS) are responsible for intoxication involving the cardiovascular and respiratory systems. Among NPS, synthetic cannabinoids (SCs) provoked side effects in humans characterized by tachycardia, arrhythmias, hypertension, breathing difficulty, apnoea, myocardial infarction, and cardiac arrest. Therefore, the present study investigated the cardio-respiratory (MouseOx Plus; EMKA electrocardiogram (ECG) and plethysmography TUNNEL systems) and vascular (BP-2000 systems) effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 140 publications
3
11
0
Order By: Relevance
“…It is well known that CB1 receptor binding is the main cause of the effects induced by JWH-018 in preclinical models. In fact, numerous previous studies have shown that pretreatment with AM-251 prevented these effects [21,30], thus confirming the involvement of CB1 receptors that are highly expressed in CNS of rodents [31]. Centrally, CB1 receptors can also modulate cardiac and vascular functions involving the medulla and dorsal periaqueductal gray (dPAG) [32,33].…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…It is well known that CB1 receptor binding is the main cause of the effects induced by JWH-018 in preclinical models. In fact, numerous previous studies have shown that pretreatment with AM-251 prevented these effects [21,30], thus confirming the involvement of CB1 receptors that are highly expressed in CNS of rodents [31]. Centrally, CB1 receptors can also modulate cardiac and vascular functions involving the medulla and dorsal periaqueductal gray (dPAG) [32,33].…”
Section: Introductionmentioning
confidence: 76%
“…Even bradycardic and hypotensive responses have been reported after SCs assumption, especially among the third-generation SCs [12,14,20]. Preclinical in vivo studies mainly revealed that synthetic cannabinoid-induced effects are bradycardia, bradyarrhythmias with sudden tachyarrhythmias, hypertension, and bradypnea [19], as our recent JWH-018 study also demonstrated [21]. Moreover, previous studies in rodents confirmed these effects after JWH-018 administration [22,23] as well as after administration of other SCs (i.e., CP-55,920 or AKB48) [24,25].…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations